Pengaruh Manajemen Laba Terhadap Penghindaran Pajak - Prestasila Esa Hariseno; Pujiono Pujiono (Universitas Muhammadiyah Enrekang, 2021)
This study aims to examine the effect of Earnings Management and Enterprise Ownership on Tax Avoidance. Earnings management can occur because the enterprise's management wants to take advantage of accounting policies in accordance with the character of the assets owned by the enterprise. Tax Avoidance can occur when companies take advantage of loopholes in tax rules to relieve a enterprise’s taxes. Agency Theory is used to examine the effect of Earnings Management on Tax Avoidance. Positive Accounting Theory is used to examine the effect of Enterprise Ownership on Tax Avoidance. This study uses the Modified Jones Model approach in determining earnings management proxy and uses the Effective Tax Rate (ETR) approach to measure Tax Avoidance. The population of this study were 168 manufacturing companies listed on the Indonesia Stock Exchange during 2014-2018 and the sample selection was carried out through purpose sampling with a total sample of 73 companies. This study was tested using descriptive statistics, multiple linear regression, T test, and R test. The implication of this research is that tax becomes one of the deduction elements in the context of management who wants to optimize company profits, by utilizing the grey area in tax regulations and accounting standards that will be used by companies to carry out tax avoidance as effectively as possible.